2022
DOI: 10.3390/nu14112221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Supplementation Alone and Combined with Resistance Exercise on Skeletal Muscle in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Sarcopenia negatively affects skeletal muscle mass and function in older adults. Omega-3 (ω-3) fatty acid supplementation, with or without resistance exercise training (RET), is suggested to play a role as a therapeutic component to prevent or treat the negative effects of sarcopenia. A systematic review and meta-analysis were conducted on the impact of ω-3 fatty acid supplementation with or without RET on measures of muscle mass and function in older adults (≥55 y). The data sources included SPORTDiscus, PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 56 publications
6
38
0
1
Order By: Relevance
“…Notably, our observed FOS-mediated strength increases compared to other studies are ostensibly due to the skeletal muscle LC n-3 PUFA incorporation, likely facilitated by our more optimal dosing regimen. In line with our results, a recent systematic review and meta-analysis, albeit in older adults, found that FOS does not increase LBM; however, it does improve strength with or without RET [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, our observed FOS-mediated strength increases compared to other studies are ostensibly due to the skeletal muscle LC n-3 PUFA incorporation, likely facilitated by our more optimal dosing regimen. In line with our results, a recent systematic review and meta-analysis, albeit in older adults, found that FOS does not increase LBM; however, it does improve strength with or without RET [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since plateau effects of protein anabolism are known [ 12 ], one explanation may be that maximal rates of muscle protein synthesis were already reached with protein intakes above 1.5 g/kg bw in both our protein-enriched groups. Furthermore, a recent meta-analysis concluded that omega-3 supplementation improves leg strength, but to a lesser extent when combined with resistance exercise, since exercise is already a strong anabolic stimulus [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a diet-induced higher inflammatory burden is associated with systemic inflammation [ 14 ] as well as with reduced muscle mass and function in healthy old adults [ 15 ]. Omega-3 fatty acids have anti-inflammatory properties and have been shown to improve leg strength and CRT time in old adults [ 16 ]. Smith et al [ 17 ] experimentally demonstrated that omega-3 supplementation (3.4 g/day) potentiates muscle protein synthesis in old adults following a hyper-aminoacidemic, hyper-insulinemic clamp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, omega-3 polyunsaturated fatty acids (such as alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA)) decrease the adverse effects of sarcopenia by reducing inflammation [ 38 ] and improving muscle strength and function in older adults with little effect on muscle mass [ 39 ]. In fact, eicosapentaenoic has been shown to have benefits against muscular atrophy caused by palmitic acid accumulation.…”
Section: Inflammation In Sarcopeniamentioning
confidence: 99%